2014
DOI: 10.1007/s00395-014-0435-8
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of Hippo/YAP signaling in the development of hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is a leading cause of heart failure and sudden death in adolescents and young adults. Recently, the role of the Hippo/YAP pathway has been investigated in the pathogenesis of HCM, although the detailed molecular mechanisms largely remain elusive. In this study, we demonstrated an up-regulation of YAP mRNA and protein levels in both HCM patient samples and transverse aortic constriction murine models as well as reduced phosphorylation of YAP at serine 127 accompanied by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 39 publications
4
47
0
Order By: Relevance
“…5 In addition, human hypertrophic cardiomyopathy patients showed Yap activation in the heart. 87 These results are consistent with the notion that inhibition of the Hippo pathway and activation of Yap may induce cardiac hypertrophy.…”
Section: Hypertrophysupporting
confidence: 88%
See 1 more Smart Citation
“…5 In addition, human hypertrophic cardiomyopathy patients showed Yap activation in the heart. 87 These results are consistent with the notion that inhibition of the Hippo pathway and activation of Yap may induce cardiac hypertrophy.…”
Section: Hypertrophysupporting
confidence: 88%
“…Third, activation of Yap is observed in human patients with hypertrophic cardiomyopathy. 87 In this condition, does inhibition of Yap ameliorate the progression of cardiomyopathy? Because Yap is involved in tumorigenesis, small molecule inhibitors of Yap are being developed.…”
Section: Discussionmentioning
confidence: 99%
“…Notablely, phosphorylated FoxO3a by PI3K/Akt signaling, was recently proved to bind the promoter of YAP, and then activated Hippo/YAP signaling [27]. And the activation of Hippo/YAP signaling was previously demonstrated to promote the cytoplasmic translocation of Smad3 from nuleues to relay cell density information in TGF-β-mediated epithelial-tomesenchymal transition [28].…”
Section: Discussionmentioning
confidence: 99%
“…In cardiomyocytes cultured in vitro , expression of YAP increased cell size and knockdown of YAP attenuated phenylephrine induced cardiomyocyte hypertrophy 170 . Interestingly, it was recently reported that YAP expression is enhanced while YAP phosphorylation is dampened with reduced Mst1 expression in myocardium of patients with hypertrophic cardiomyopathy 174 , suggesting a role of YAP in pathogenesis of human hypertrophic heart disease. Taken together, functions of YAP and the Hippo pathway in cardiac hypertrophy might be more complex and context-dependent.…”
Section: The Hippo Pathway In Cardiac Hypertrophy and Dilated Cardiommentioning
confidence: 99%